FLUORESCENCE DIAGNOSIS OF BLADDER CANCER WITH AGENT HEXASENS – THE RESULTS OF MULTICENTER TRIAL - E. V. Filonenko; A. D. Kaprin; B. Ya. Alekseev; V. I. Ivanova-Radkevich; E. K. Slovokhodov; V. L. Filinov; A. N. Urlova (Biomedical Photonics)
The results of multicenter trial for efficacy of fluorescence diagnosis for bladder cancer with agent hexasens (SSC Scientific Research Institute Organic Intermediates and Dyes, Russia) based on hexyl ester of 5-aminolevulinic acid compared with routine cystoscopy are represented in the article. The study included 124 patients. All patients had intravesical instillation of 50 ml of 0,2% hexasens. The exposure time accounted for 1-2 h. After removal of the drug from bladder standard cystoscopy followed by fluorescence diagnosis was performed in every patient. During the local fluorescence spectroscopy the intravesical instillation of the agent hexasens was shown to induce selective accumulation of photoactive protoporphyrin IX in tumor cells comparing with intact bladder mucosa. During 1 h after intravesical instillation of hexasens solution the level of fluorescence of hexasens-induced protoporphyrin IX in the tumor was higher than that in surrounding intact mucosa at average in 5.8 fold. As compared with results of standard cystoscopy, fluorescence diagnosis improved the sensitivity of the method by 24.4% (from 75.6% to 100%), the accuracy – by 15.2% (from 83.3% to 98.5%) and negative predictive value – by 33.5% (from 66.5% to 100%). Fluorescence diagnosis gave an opportunity to detect additional tumor foci, which were invisible in white light, in 27.4% of patients. For fluorescence diagnosis in 4.0% of patients false-positive fluorescence of bladder mucosa was detected that was probably due to inflammation. None of patients received active dose of the drug hexasens had adverse reactions, changes in general well-being and blood and urine parameters. According to the results of the study fluorescence diagnosis with hexasens for bladder cancer is recommended for use in clinical practice.